MOTIVASI DALAM KASUS PEMERKOSAAN (PERSPEKTIF GENDER) - Supomo Ari Sasongko (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
The rapes is a serious form of sexual crimes, so that rape has been defined as a form of sexual criminal offense. Real rape case comes down to the issue of motivation of the perpetrator. Results of research and analysis indicate that the rape victim offender motivation was very diverse and influenced by internal and external factors. Cases of rape are also related to the issue of inequality of gender relations, ie, sub-ordinated, steorotipe and gender-based violence.